The effect of six-week regular stretching exercises on regional and distant pain sensitivity: an experimental longitudinal study on healthy adults - Morten Pallisgaard Støve; Janus Laust Thomsen; Stig Peter Magnusson; Allan Riis (BMC, 2024)
Abstract Background Stretching exercises are widely used for pain relief and show positive effects on musculoskeletal, nociplastic and neuropathic pain; the magnitude of altered pain sensitivity responses following regular stretching is currently unknown. This study aimed to investigate the effect of six weeks of regular stretching exercise on regional and widespread pain sensitivity and range of motion and the effect of stretching cessation on regional and widespread pain sensitivity and range of motion. Methods An experimental single-blind longitudinal repeated measures study. Twenty-six healthy adults were recruited. Regional and distant pressure pain thresholds and passive knee extension range of motion were measured at three points: before (baseline) and after six weeks (post-stretch) of daily bilateral hamstring stretching exercises and following four weeks of cessation (post-cessation) from stretching exercises. Results Participants had a mean ± standard deviation (range) age of 23.8 ± 2.1 (21-30) years. There was a 36.7% increase in regional (p = 0.003), an 18.7% increase in distant pressure pain thresholds (p = 0.042) and a 3.6% increase in range of motion (p = 0.002) between baseline and post-stretch measures. No statistically significant differences were found for regional (p = 1.000) or distant pressure pain thresholds (p = 1.000), or range of motion (p = 1.000) between post-stretch and post-cessation. A 41.2% increase in distant pressure pain thresholds (p = 0.001), a 15.4% increase in regional pressure pain thresholds from baseline to post-cessation (p = 0.127) and a 3.6% increase in passive knee extension range of motion (p = 0.005) were found from baseline to post-cessation. Conclusions Six weeks of regular stretching exercises significantly decreased regional and widespread pain sensitivity. Moreover, the results showed that the hypoalgesic effect of stretching on regional and widespread pain sensitivity persisted following four weeks of cessation. The results further support the rationale of adding stretching exercises to rehabilitation efforts for patients experiencing nociceptive, nociplastic, and neuropathic pain. However, further research is needed to investigate how the long-term effects of stretching exercises compare with no treatment in clinical populations. Trial registration The trial was registered June 1st, 2021 at ClinicalTrials.gov (Trial registration number NCT04919681).